Regulation matters: A comparison of Malaysian-Indonesian's e-hailing regulation framework - Chee, Dorothea Ke Jing (2019)
E-hailing, which is also known as ride-hailing or ride-sourcing, has been on the rise across the globe. However, it is known as a disruptive innovation as unregulated services have triggered major disruptions and led to certain setbacks in the transportation industry. It has been blamed for the rise in privacy and safety issues, unfair business competition and a decline in demand in the traditional taxi industry. In response to these issues, certain countries have started to regulate the e-hailing industry. The objective of this study is to identify, analyze and contrast on the form and enforcement of Malaysian-Indonesian's e-hailing regulation framework by using qualitative-comparative research. In this study, literature have been gathered from credible online sources. Based on the results of the study, there are commonalities and differences between the Malaysian and Indonesian's e-hailing regulation framework. For instance, both countries do have similar form and enforcement of regulations and policies in regulating the e-hailing industry, and the major difference would be on the data protection law. Furthermore, implications of the study have been discussed based on two aspects such as policy makers and individuals. For instance, just as the saying goes, “innovation outpaces regulation”. The current state of the e-hailing industry is underregulated rather than unregulated. Policy makers should seek to improve existing regulation framework rather than starting new regulations from ground up to minimize the risk of overregulation that might eventually diminish the industry.